A new species of Allocoelia Mocsáry, 1889 from South Africa. (Hymenoptera: Chrysididae). - Niehuis, Oliver (Contributions to Entomology = Beiträge zur Entomologie, 2000)
Allocoelia kuhlmanni nov. spec. is described from South Africa. The new species belongs to the glabra group. Drawings of the lateral propodeal tooth and the genital capsule are included in the description. The phylogenetic relationships of the new species are discussed.Nomenclatural Actskuhlmanni Niehuis, 2000 (Allocoelia), spec. n.